Diffusivity and Sorptivity of Berea Sandstone Determined using Neutron Radiography. Issue 3 (8th March 2013) - Kang, M.; Perfect, E.; Cheng, C.L.; Bilheux, H.Z.; Gragg, M.; Wright, D.M.; Lamanna, J.M.; Horita, J.; Warren, J.M.
Abstract : Neutron radiography is increasingly being used to study the dynamics of water movement in variably saturated porous media. It has been applied to visualize water imbibition in both natural and engineered materials, including soil, rock, brick, concrete, and glass. The sorptivity, S, and unsaturated diffusivity, D (θ), are important parameters for describing water movement under partially saturated conditions. Estimates of S and D (θ) have been obtained using a variety of techniques, including neutron imaging. However, we could find no previous reports of such measurements for the Berea sandstone, regardless of the method employed. Berea sandstone is a widespread, medium‐ to fine‐grained terrestrial sandstone of Mississippian age that is used extensively as a standard porous medium in the geology and petroleum engineering fields. We used the CG‐1D neutron imaging facility at the High Flux Isotope Reactor of Oak Ridge National Laboratory to estimate S and D (θ) from radiographs acquired every 26 s. A 25 μm thick LiF/ZnS scintillator was employed in conjunction with a DW936 IkonL ANDOR charge coupled device (CCD) camera system, giving a spatial imaging resolution of ∼75 μm. Four replicate cores were investigated. The positions of the observed wetting fronts were linearly regressed against the square root of time. Sorptivity values calculated from the slopes of these relations ranged from 0.89 to 1.46 mm s −1/2 . Further analysis yielded D (θ) functions. These functions were very reproducible and showed good agreement with independent D (θ) values calculated from relative permeability and capillary pressure‐saturation data for Berea sandstone. To the best of our knowledge, these are the first published estimates of S and D (θ) for Berea sandstone. Our results clearly demonstrate the effectiveness of neutron imaging in providing high quality, quantitative data for the computation of unsaturated flow parameters.